Teaching Excellence: A Reaction to the Smith Commission Report and its Effects - Samad, D. R.; Fraser, I. H.; Fish, T. A.; Fraser, L. D. (Canadian Journal of Higher Education, 1995)
This paper has been written partially in response to the Smith Commission Report, and partially in response to the reactions the report has elicited already. The Smith Commission Report voiced many valid concerns about teaching excellence; however, many of the so-called "innovations" that have been developed in answer to Stuart Smith’s call for teaching excellence are, in fact, little different from those techniques implemented under the auspices of the Ontario Universities Program for Institutional Development (OUPID) in the 1960’s and early 1970’s. This being the case, the authors feel that the most likely result will be a similar lack of success. It is, therefore, our suggestion that an attempt ought to be made to change the infrastructure of the university sys- tem so that it supports good teaching and research with equal measure. This, above all else, should lead to real improvements in the quality of teaching.